Observation of mortality in extremely preterm newborns related to conditions of low or high oxygen supplementation beyond the target saturation range: A literature review - Bertoncelo, Jaqueline Fernanda Felix; Oliveira, Alex (Seven Editora, 2023)
Prematurity is defined as a birth that occurs before 37 gestational weeks, and is often associated with the need for oxygen supplementation, however the saturation target of this population is debatable and is still widely debated, and some negatives were pointed out. This study aims to systematically review the available literature and evaluate the mortality associated with a target range of low and high saturation in extremely premature newborns, and the associated secondary ones as their respective pre-established saturation ranges. A review was performed based on eligible studies found through searches in the Pubmed and Scielo databases. Some negatives were pointed out, such as retinopathy of prematurity, cerebral palsy, neurodevelopmental impairment, septicemia, necrotizing enterocolitis, persistent increase in systolic blood pressure in adulthood, long-term bronchial hyperreactivity and death. Mortality is often related to lower saturation levels, making it relevant to understand this association to better define a target saturation range that minimizes related complications in this population. DOI:https://doi.org/10.56238/sevened2023.004-028